The Establishment of the Eucharist in the Process of the Foundation of the Church - Rabczyński, Paweł (Studia Warmińskie, 2020)
The contemporary ecclesiology emphasises the Church-building character of the life of Jesus Christ. The genesis of the Church is not linked with a single event. The foundation of the Ecclesia belongs to the trinitarian economy of God and is a dynamic process. One can distinguish between ten different stages of ecclesiogenesis, including two key ones that prove the founding initiative of Jesus. The first one is Simon Peter’s confession of messianic faith in the vicinity of Caesarea Philippi, which results in the Master giving him a new name and proclaiming the foundation of the Ecclesia. The second one is the establishment of the Eucharist. During the Last Supper Jesus celebrated Passover with the Twelve. In this way, He anticipated His death upon the cross as a voluntary propitiation. By referring to the symbolism of the passover feast and the books of the Old Testament, He explained the meaning of His death – reassembling Israel in the light of the coming of the kingdom of God. He makes a new Covenant “in His own blood”, owing to which all people have a chance for salvation. In this way, He founded the People of God of the ultimate times – the Church.